2023
DOI: 10.3390/plants12020339
|View full text |Cite
|
Sign up to set email alerts
|

Natural Active Ingredients and TRPV1 Modulation: Focus on Key Chemical Moieties Involved in Ligand–Target Interaction

Abstract: Diseases such as cancer, neurological pathologies and chronic pain represent currently unmet needs. The existing pharmacotherapeutic options available for treating these conditions are limited by lack of efficiency and/or side effects. Transient receptor potential vanilloid 1 ion channel emerged as an attractive therapeutic target for developing new analgesic, anti-cancer and antiepileptic agents. Furthermore, various natural ingredients were shown to have affinity for this receptor. The aim of this narrative … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 170 publications
0
2
0
Order By: Relevance
“…One of the suggested mechanisms is that vanilloids and their counterparts bind to transient receptor potential vanilloid 1 (TRPV1) [ 41 ]. TRPV1 is primarily expressed in sensory neurons, but it has also been found in non-neuronal cells and immune cells such as dendritic cells, macrophages, and T-cells [ 41 , 42 ]. The difference in TRPV1 expression levels between macrophages and epithelial cells could be one of the reasons why we observe a slightly different immunomodulatory potential of these small molecules in different cell lines.…”
Section: Discussionmentioning
confidence: 99%
“…One of the suggested mechanisms is that vanilloids and their counterparts bind to transient receptor potential vanilloid 1 (TRPV1) [ 41 ]. TRPV1 is primarily expressed in sensory neurons, but it has also been found in non-neuronal cells and immune cells such as dendritic cells, macrophages, and T-cells [ 41 , 42 ]. The difference in TRPV1 expression levels between macrophages and epithelial cells could be one of the reasons why we observe a slightly different immunomodulatory potential of these small molecules in different cell lines.…”
Section: Discussionmentioning
confidence: 99%
“…Blockage of TRPV1 led to significant inhibition of joint pain and proved to be a promising therapeutic against osteoarthritis ( 53 ). Various agonists of TRPV1, such as capsaicin, resiniferatoxin, allicin, gingerol, and piperine, have been shown to interact and bind to TRPV1 ( 54 , 55 ). Several clinical studies have shown the effect of topical or intra-articularly administered capsaicin in alleviating OA-related pain ( 56 , 57 ).…”
Section: Molecular Pathways Involved In Osteoarthritis Pathophysiologymentioning
confidence: 99%